2001
DOI: 10.1111/j.1651-2227.2001.tb00787.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of iron deficiency in 12‐mo‐old infants from 11 European areas and influence of dietary factors on iron status (Euro‐Growth study)

Abstract: A prospective longitudinal cohort study was performed to assess the prevalence of iron deficiency in European infants at 12 mo of age, and to study the influence of socio‐economic status, dietary factors, growth and morbidity on iron status. The cohort consisted of 488 normal term infants from primary healthcare centres in 11 European areas. Assessed were socio‐economic variables, dietary intake, anthropometry and morbidity at regular intervals from birth to 12 mo, and haemoglobin, serum ferritin, mean corpusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
7

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 28 publications
4
40
0
7
Order By: Relevance
“…This analysis is not supported by convincing research data arising from plasma measurements of nutrients of interest, with the notable exceptions of Fe (8) and vitamin D (9,10) . Energy and macronutrient consumption was identical in the two groups in the present study with the exception of protein, for which the consumption was higher in Group CM, cows' milk being one possible but not exclusive causative factor.…”
Section: Discussionmentioning
confidence: 80%
“…This analysis is not supported by convincing research data arising from plasma measurements of nutrients of interest, with the notable exceptions of Fe (8) and vitamin D (9,10) . Energy and macronutrient consumption was identical in the two groups in the present study with the exception of protein, for which the consumption was higher in Group CM, cows' milk being one possible but not exclusive causative factor.…”
Section: Discussionmentioning
confidence: 80%
“…These numbers are comparable to data collected in other industrialized countries. 13,14 Related to the problem of ID/IDA is the interaction of iron and lead. Results of both animal and human studies have confirmed that IDA increases intestinal lead absorption.…”
Section: Prevalence Of Id and Idamentioning
confidence: 99%
“…48 Na impossibilidade da continuidade do aleitamento materno, a substituição desse por leite de vaca é fator de risco para deficiência de ferro, e a substituição por fórmula infantil modificada é fator de proteção. [49][50][51][52][53] Entre 4 e 6 meses ocorre gradualmente o esgotamento das reservas de ferro, e a alimentação complementar passa a ter papel importante na prevenção da deficiência de ferro e outros micronutrientes. 26,40,50,[54][55][56] Os requerimentos de ferro em relação à energia ingerida, nessa idade, são os mais altos, com exceção do último trimestre gestacional.…”
Section: Grupo Vulnerável: Crianças Menores De 24 Mesesunclassified
“…[49][50][51][52][53] Entre 4 e 6 meses ocorre gradualmente o esgotamento das reservas de ferro, e a alimentação complementar passa a ter papel importante na prevenção da deficiência de ferro e outros micronutrientes. 26,40,50,[54][55][56] Os requerimentos de ferro em relação à energia ingerida, nessa idade, são os mais altos, com exceção do último trimestre gestacional. É possível atingir esse requerimento de ferro se a dieta contiver considerá-veis quantidades de carne, vitamina C e produtos enriquecidos; no entanto, em países em desenvolvimento, a alimentação complementar pode não fornecer o ferro suficiente e, assim, a criança precisar de alguma forma de complementação para prevenir a deficiência de ferro.…”
Section: Grupo Vulnerável: Crianças Menores De 24 Mesesunclassified